Numerical Analysis of the Factors about Combustion Stability on Boiler - Li Jun Li Jun; Yan Weiping; Gao Yang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Through the research of the coal pulverized catches fire and steadily combustion mechanism, the numerical simulation of the 300MW tangentially pulverized coal fired boiler by Coal-fire software, and combine the operating data of the boiler, the corresponding relation between the result of numerical simulation and combustion stability have been established. The result indicates that the higher volatile matter, lower content of ash and moisture of the coal, it helps the coal pulverized air current to catch fire. More fineness coal pulverized is favorable to catch fire. When boiler load reduced, it will influence the characteristic"lighted by itself" of the tangentially pulverized coal fired boiler, and it will cause combustion unstably.